EFFICACY, SAFETY, AND FUTURE DIRECTIONS OF ADVANCED THERAPY METHODS FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASES - Kulchytska, O.M.; Kuzminova, N.V.; Lozinsky, S.E.; Kniazkova, I.I.; Khomenko, V.M.; Shkarivsky, Yu.L.; Velychkovych, M.M. (World of Medicine and Biology, 2025)
Crohn’s disease and ulcerative colitis are the most common inflammatory bowel diseases. They are chronic diseases characterized by inflammation of the gastrointestinal tract that lead to poor quality of life and disability for patients around the world. The number of people with inflammatory bowel disease worldwide is approximately five million, however, the exact number is unknown, as prevalence data may vary depending on the level of health care, diagnosis, and access to treatment in different countries. The causes of these diseases are multifactorial, but one of the main ones is dysregulation of the immune system. Treatment of such patients is aimed at achieving and maintaining periods of remission. The development of newer therapies, including biologics and oral small molecules, targets different immune response mechanisms, opening up new opportunities for treatment. New therapies can significantly improve the quality of life by helping to achieve and maintain remission. However, their cost remains an important aspect that needs to be addressed in the context of treatment accessibility.